2022
DOI: 10.1093/neuonc/noac180
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of intrathecal administration of trastuzumab in patients with HER2-positive breast cancer with leptomeningeal metastasis

Abstract: Background Patients with HER2-positive breast cancer (HER2+BC) develop central nervous system metastases twice as often as patients with luminal HER2-negative breast cancer. Leptomeningeal progression results in a drastically altered prognosis with limited therapeutic options. This phase II study was conducted in order to assess the efficacy of intrathecal (IT) trastuzumab in HER2+BC patients with leptomeningeal metastasis (LM), based on a phase I dose-escalation study that had determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 32 publications
0
31
0
14
Order By: Relevance
“…However, it is not clear whether these results can be reproduced with photon radiotherapy (LoE 2b/ B/AGO+/−). Patients with HER2+ disease may benefit from intrathecal administration of trastuzumab based on recent studies demonstrating improved outcome (LoE 3a/C/AGO+/−) [29,30].…”
Section: Cns Metastasesmentioning
confidence: 99%
“…However, it is not clear whether these results can be reproduced with photon radiotherapy (LoE 2b/ B/AGO+/−). Patients with HER2+ disease may benefit from intrathecal administration of trastuzumab based on recent studies demonstrating improved outcome (LoE 3a/C/AGO+/−) [29,30].…”
Section: Cns Metastasesmentioning
confidence: 99%
“…In the patient cohort of Zagouri et al, 21.7% had previously received methotrexate administered either intravenously or intrathecally [15]. Only 34.5% of patients in the study by Zagouri et al and 32% in the phase II study received no additional therapy for meningeal carcinomatosis during IT trastuzumab therapy [15,17]. In addition to IT trastuzumab, most cases in the study by Zagouri et al and the study by Oberkampf et al received some form of systemic therapy consisting of chemotherapy, endocrine or anti-HER2 targeted therapy as well as radiotherapy of the brain.…”
Section: Trastuzumabmentioning
confidence: 99%
“…Zu den Nebenwirkungen, die möglicherweise mit der Behandlung zusammenhängen, gehörten: Kopfschmerzen, Krampfanfälle und allergische Reaktionen. Diese sind jeweils in 5% der Fälle aufgetreten [17] [20,23]. Die Validierung des Curie-Score veranschaulichte allerdings die Schwierigkeit der Erstellung eines universell anwendbaren Prognosescores für eine Erkrankung, zu der solch eine geringe Datenmenge existiert [23].…”
Section: Trastuzumabunclassified
See 1 more Smart Citation
“…To overcome this limit, a clinical study evaluated the efficacy of intrathecal administration of Trastuzumab in patients with HER2-positive leptomeningeal metastases. The results demonstrated that intrathecal Trastuzumab administration could be a viable option for HER-positive patients [ 48 , 49 ]. A meta-analysis of 12 phases II clinical trials demonstrated the beneficial effect of Lapatinib, a double epidermal growth factor receptor (EGFR) and HER2 inhibitor, in patients with progressive HER2-positive CNS metastases.…”
Section: Strategies For Targeting Malignant Brain Tumors With Kinase ...mentioning
confidence: 99%